The Subjectivity and the Action - Álvarez Rodríguez, Miguel Ángel (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2015)
This paper seeks to explain what is subjectivity and action in its individual and social aspects and for them it is necessary to consider how the human being and the other's need for such personal conformation is formed. Thanks to the language and the presence of the other can establish a set of plausible assumptions that explain how to carry out the action in humans. The paper presents the anthropological element allowing arrives at an understanding of the action, essential to understand how changes in society are generated.